Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.molpharmaceut.7b00797
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Flavonoid Naringenin Regulates the Expression of LXRα in THP-1 Macrophages by Modulating AMP-Activated Protein Kinase

Abstract: The present work investigates the modulation of grapefruit flavonoid naringenin over liver X receptor alpha (LXRα) and its target genes in THP-1 macrophages, focusing on AMP-activated protein kinase (AMPK) implication. Naringenin induced LXRα at mRNA and protein levels besides influencing the expression of LXRα target genes ABCA1, ABCG1 (ATP-binding cassette A1 and G1), and SREBP1c (sterol response element binding protein 1c) in THP-1 macrophages. The increased LXRα mRNA and protein expression was reverted whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
(117 reference statements)
0
22
0
2
Order By: Relevance
“…The flavonoids naringenin, 339 quercetin, 358 and vitexin 359 increased ABCA1 / Abca1 mRNA 339 , 359 and ABCA1 protein levels 339 , 360 , 358 by induction of LXRA/ Lxra mRNA 358 , 359 and LXR-α protein. 339 , 360 The effect of naringenin and the standard ABCA1 / Abca1 inducer TO901317 were additive. Naringenin was shown to be dependent on the cAMP-activated protein kinase (AMPK) regulation ( AMPK ), as well as SREBP1C regulation.…”
Section: Part I: Status Quomentioning
confidence: 97%
“…The flavonoids naringenin, 339 quercetin, 358 and vitexin 359 increased ABCA1 / Abca1 mRNA 339 , 359 and ABCA1 protein levels 339 , 360 , 358 by induction of LXRA/ Lxra mRNA 358 , 359 and LXR-α protein. 339 , 360 The effect of naringenin and the standard ABCA1 / Abca1 inducer TO901317 were additive. Naringenin was shown to be dependent on the cAMP-activated protein kinase (AMPK) regulation ( AMPK ), as well as SREBP1C regulation.…”
Section: Part I: Status Quomentioning
confidence: 97%
“…Naringenin upregulated LXRα at mRNA and protein levels and its target genes in an AMPK dependent manner in THP1 macrophages (Kemmerer, Wittig, Richter, Brüne, & Namgaladze, 2016;Saenz et al, 2017).…”
Section: Naringeninmentioning
confidence: 98%
“…Naringenin is found in oranges and grapefruits and is one of the major citrus flavanones (Saenz et al, 2017). Preclinical studies showed that naringenin increased the levels of HDL and LPL in Wistar rats, which were fed with ethanol alone, and can efficiently prevent the accumulation of plasma lipids and lipoproteins (Jayachitra & Nalini, 2012).…”
Section: Naringeninmentioning
confidence: 99%
“…Real-time RT-PCR was performed with a Quanti-Fast SYBR Green PCR kit, using a StepOnePlus Real-time PCR machine (Applied Biosystems, Foster City, CA, United States). Primers for the following target genes ICAM-1 and MCP-1 were obtained from a previously published report : ABCA-1 (Moss, 2018), CD36, SR-A (Xu et al, 2006), and LXR-α (Saenz et al, 2018), and the housekeeping gene glyceraldehyde-3phosphate dehydrogenase (GAPDH) was obtained from the work of . Primer details are listed in Table 1.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%